Aristotelian Thought In Eastern Peripatetics: Farabi And Ibn Sina’s Philosophical Adaptations - Akhatova Dildora Akhtamovna (American Journal Of Social Sciences And Humanity Research, 2025)
This article examines the adaptation and transformation of Aristotelian philosophy by the Eastern peripatetic philosophers, Farabi and Ibn Sina. Special attention is paid to their interpretation of metaphysical, cosmological, and ontological concepts, revealing a blend of ancient Greek philosophical approaches with new frameworks characteristic of Islamic thought.